2013
DOI: 10.3390/molecules18043859
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-DAD-ESI/MS Identification and Quantification of Phenolic Compounds in Ilex paraguariensis Beverages and On-Line Evaluation of Individual Antioxidant Activity

Abstract: “Chimarrão” and “tererê” are maté (dried, toasted and milled Ilex paraguariensis leaves and stemlets) beverages widely consumed in South America. This paper describes the application of HPLC-DAD-ESI/MS method for the identification and quantification of caffeoylquinic acids (CQA), flavonol glycosides and purine alkaloids in these beverages. The beverage samples were prepared from commercial lots of maté from Southern Brazil. The caffeoylquinic acids, 4,5-diCQA, 3-CQA, 5-CQA, and 4-CQA were the major compounds,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 30 publications
3
26
0
Order By: Relevance
“…Peres et al (2013) found caffeine concentrations up to 268 mg/mL in mate samples, but the compounds found in higher concentrations were caffeoylquinic acids with concentrations up to 289 mg/mL. Table 3 shows the concentration of the eight compounds quantitatively identified by GC/MS, with caffeine as the major compound.…”
Section: Resultsmentioning
confidence: 99%
“…Peres et al (2013) found caffeine concentrations up to 268 mg/mL in mate samples, but the compounds found in higher concentrations were caffeoylquinic acids with concentrations up to 289 mg/mL. Table 3 shows the concentration of the eight compounds quantitatively identified by GC/MS, with caffeine as the major compound.…”
Section: Resultsmentioning
confidence: 99%
“…Yerba mate (Ilex paraguariensis St. Hilaire) is a food that has been highlighted as a dietary source of phenolic compounds, especially chlorogenic acids, a family of compounds formed by isomers of esters of caffeic acid with quinic acid (Marques & Farah, 2009;Peres, Tonin, Tavares, & Rodriguez-Amaya, 2013). The literature also reports the presence of gallic acid, caffeic acid, syringic acid, ferulic acid, p-coumaric acid and rutin (Bizzoto et al, 2012;Frizon, Perusselli, Sturion, Fracasso, & Hoffman-Ribani, 2015;Nunes et al, 2015;Pagliosa et al, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…For this type of experiment, the concentration used for the organic solvent (methanol or acetonitrile) in the mobile phase ranged between 40% and 85% (Anesini, Turner, Cogoi, & Filip, 2012;Dugo et al, 2009;Dutra & Ribani, 2010;Filip, Lopéz, Giberti, Coussio, & Ferraro, 2001;Heck, Schmalko, & Meija, 2008;Isolabella et al, 2010;Pagliosa et al, 2010;Peres et al, 2013;Valerga, Reta, & Lanari, 2012;Nunes et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of different extraction conditions on the phenolic components of I. paraguariensis including their quantities have been previously reported (Grujic et al 2012;Peres et al 2013;Bae et al 2015). However, there are very few literature reports on the optimization of both the antioxidant and PL inhibitory activity of I. paraguariensis extracts using RSM.…”
Section: Introductionmentioning
confidence: 98%
“…Typical maté beverages consumed in Brazil are ''chimarrão'' and ''tererê'' (prepared with hot and cold water, respectively) (Peres et al 2013). Recently, maté has been studied for its potential beneficial effects in the treatment of obesity (Bracesco et al 2011).…”
Section: Introductionmentioning
confidence: 99%